Head and neck cancer: improving outcomes with a multidisciplinary approach - Lo Nigro, Cristiana (Cancer Manag Res, 2017)
For early-stage head and neck cancer (HNC), surgery (S) or radiotherapy (RT) is a standard treatment. The multidisciplinary approach, which includes multimodality treatment with S followed by RT, with or without chemotherapy (CT) or concurrent chemoradiotherapy (CRT), is required for locally advanced head and neck cancer (LAHNC). CRT improves prognosis, locoregional control (LRC), and organ function in LAHNC, compared to RT alone. Prognosis in recurrent/metastatic HNC (R/M HNC) is dismal. Platinum-based CT, combined with the anti-Epidermal Growth Factor Receptor (EGFR) antibody (Ab) cetuximab, is used in first-line setting, while no further validated options are available at progression. The complexity of disease is, in part, due to the heterogeneity of organs and functions involved and the need for a multimodality approach. In addition, the patient population (often elderly and/or patients with smoking and alcohol habits) argues for an individually tailored treatment plan. Furthermore, treatment goals – which include cure, organ, and function preservation, quality of life and palliation – must also be considered. Thus, optimal management of patients with HNC should involve a range of healthcare professionals with relevant expertise. The purpose of the present review is to 1) highlight the importance and necessity of the multidisciplinary approach in the treatment of HNC; 2) update the knowledge regarding modern surgical techniques, new medical and RT treatment approaches, and their combination; 3) identify the treatment scenario for LAHNC and R/M HNC; and 4) discuss the current role of immunotherapy in HNC.